2008
DOI: 10.2500/ajr.2008.22.3152
|View full text |Cite
|
Sign up to set email alerts
|

The use of Portable Intraoperative Computed Tomography Scanning for Real-Time Image Guidance: A Pilot Cadaver Study

Abstract: Intraoperative portable CT scanning with real-time IGS updates is feasible and likely would add little additional time. Accuracy is improved at the skull base. Prospective studies on actual patients are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…They are also beneficial for updating anatomical information real-time for image guided surgery as suggested by Das et al [18]. In this paper, we tested the use of these scanners for image-guided surgical procedures that require submillimetric accuracy and use bone-anchors to achieve it, such as PCI.…”
Section: Discussionmentioning
confidence: 99%
“…They are also beneficial for updating anatomical information real-time for image guided surgery as suggested by Das et al [18]. In this paper, we tested the use of these scanners for image-guided surgical procedures that require submillimetric accuracy and use bone-anchors to achieve it, such as PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this technique may improve surgical results and have a future role in ablative procedures. [13][14][15] In the current study, patients were not charged for intraoperative CT scan evaluation. Otherwise, current procedural terminology codes, such as 70486 and 76380 would potentially be used for maxillary and limited CT scanning, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The setup time required to rescan the patient, process the images, and often reregister the image-guided surgery system averages between 13 and 45 minutes. 25,27 The goal of intraoperative imaging, however, is to permit more successful minimally invasive surgeries, which should effectively reduce the patient's length of hospital stay and need for revision surgery. Hall and Truwit 5 found that the length of stay was 55% shorter in those resections performed with intraoperative MRI guidance.…”
Section: Disadvantages Of Intraoperative Imagingmentioning
confidence: 99%